A Web Platform for Integrated Vulnerability Assessment and Cyber Risk Management - Pietro Russo; Alberto Caponi; Marco Leuti; Giuseppe Bianchi (Information, 2019)
Cyber risk management is a very important problem for every company connected to the internet. Usually, risk management is done considering only Risk Analysis without connecting it with Vulnerability Assessment, using external and expensive tools. In this paper we present CYber Risk Vulnerability Management (CYRVM)—a custom-made software platform devised to simplify and improve automation and continuity in cyber security assessment. CYRVM’s main novelties are the combination, in a single and easy-to-use Web-based software platform, of an online Vulnerability Assessment tool within a Risk Analysis framework following the NIST 800-30 Risk Management guidelines and the integration of predictive solutions able to suggest to the user the risk rating and classification.